Family Support and Self-Efficacy Among Post-Ischemic Stroke Patients: A Cross-Sectional Correlational Study - Riski Amalia; Nani Safuni; Asrizal Asrizal; Abul A’la Tarigan; Irfanita Nurhidayah; Dewiyuliana Dewiyuliana; Anda Kamal (Queeva Publishing, 2025)
Background: Post-ischemic stroke patients often experience residual functional limitations that affect recovery and daily functioning. Family support may influence self-efficacy during the rehabilitation process. Methods: This cross-sectional study was conducted from November to December 2023 among 193 post-ischemic stroke patients undergoing medical rehabilitation in a general Hospital in Indonesia. Samples were selected using purposive sampling. Family support was measured using a modified Family Support Instrument, and self-efficacy was assessed using the Stroke Self-Efficacy Questionnaire (SSEQ). Data were analyzed using the Spearman Rho correlation test. Results: Overall family support showed a weak positive correlation with self-efficacy (r = 0.290; p < 0.001). Informational support demonstrated a moderate positive correlation with self-efficacy (r = 0.429; p < 0.001). Appreciation support showed a weak negative correlation (r = −0.262; p < 0.001), while instrumental and emotional support were not significantly associated with self-efficacy. Conclusion: Family support is associated with self-efficacy among post-ischemic stroke patients, with informational support appearing to play a particularly important role. Strengthening family support through integration with healthcare and community-based services may enhance rehabilitation outcomes for post-ischemic stroke patients